Impact of Endometrioma Resection on Eutopic Endometrium Metabolite Contents: Noninvasive Evaluation of Endometrium Receptivity - Ersahin, Aynur; Celik, Onder; Acet, Mustafa; Ersahin, Suphan; Acet, Tuba; Bozkurt, Duygu Kara; Ilhan, Selcuk (Sage Publications Inc, 2017)
The aim of this study was to determine whether endometrioma resection alters most commonly defined endometrial metabolites, lactate (Lac), N-acetylaspartate (NAA), creatine 1 (Cr1), creatine 2 (Cr2), and choline (Cho) during the window of implantation. Twenty patients with uni- or bilateral endometrioma and 7 patients having nonendometriotic benign ovarian cyst were included. Midluteal phase magnetic resonance spectroscopy analysis of eutopic endometrium was performed before surgery. Second spectrum of endometrium was obtained 3 to 5 months after laparoscopic endometrioma resection. Pre- and postoperative endometrial peaks of Lac, NAA, Cr, and Cho were measured in units and denominated in parts per million (ppm). Compared to preoperative peak values, significantly decreased NAA, Lac, and Cr1 signals were noted in patients undergoing endometrioma surgery. Nearly 5-fold decline in the NAA signal occurred after endometrioma surgery (1.94 +/- 3.24 vs 0.37 +/- 0.55). Likewise, 2.5-fold decline in Lac signals was noted after endometrioma resection (2.81 +/- 2.64 vs 1.06 +/- 1.88). Both uni- and bilateral endometrioma affected endometrium signals the same. The peak intensity of Cho, Cr1, Cr2, NAA, and Lac did not alter significantly after nonendometriotic cyst surgery. Endometrioma surgery straightens endometrial NAA, Lac, and Cr1 peaks, suggesting improvement in endometrial receptivity.
Keywords: spectroscopy; endometrioma; eutopic endometrium; laparoscopy